Effect of surface tension, gravity and turbulence on condensation patterns of R1234ze(E) in horizontal mini/macro-channels. (October 2018) - Wen, Jian; Gu, Xin; Liu, Yuce; Wang, Simin; Li, Yanzhong
Highlights: The liquid film thickness decreased significantly when reducing the tube dimension. The surface tension plays a role to increase the heat performance. The gravity can either enhance or weaken the heat transfer coefficient during condensation flow. The turbulence in liquid films significantly reduced the local thermal resistance. The onset of turbulence inside the liquid film occur at much lower ReL for mini-channels. Abstract: The condensation patterns of R1234ze(E) in circular mini/macro-channels with diameters ranged from 0.493 to 4.57 mm was numerically investigated. The effects of mass flux, vapor quality and tube diameter on heat transfer coefficients were analyzed. The relative role of surface tension, gravity and shear stress in mini/macro-channels was explored and the turbulence effect of liquid phase was discussed. The heat transfer coefficients increased with the mass flux, vapor quality and the decrease of tube diameter. The liquid film thickness decreased significantly when reducing the tube dimension for the increased shear stress. The surface tension was found to play a role to increase the heat performance by enhancing the heat convection between liquid film and wall surface, which was only obvious in mini-channels. Contrary to the effect of surface tension, the gravity effect was negligible in mini-channels with a diameter less than 1 mm, while had an important effect on heat transfer coefficients for macro-channels. The gravity affected both liquid film distribution and velocity field, which can either enhance or weaken the heat transfer coefficient during condensation flow. The turbulence in liquid film played an important role in reducing the local thermal resistance and was more important in tubes with larger diameter. The onset of turbulence inside the liquid film may occur at much lower liquid Reynolds numbers for mini-channels.